Advances and perspectives on solid oxide fuel cells : From nanotechnology to power electronics devices - Arshad, Muhammad Sarfraz; Mbianda, Xavier Yangkou; Ali, Imran; Wanbing, Guan; Kamal, Tariq; Kauhaniemi, Kimmo; Hassan, Syed Zulqadar; Yasin, Ghulam (Wiley-VCH GmbH, 2023)
Solid oxide fuel cells (SOFCs) hold an important place in energy conversion and storage systems due to their fuel flexibility, high efficiency, and environmental sustainability. The scorching temperature (≥800 °C) to operate SOFCs results in shorter life span due to rapid deterioration of accompanying components. Nanomaterials have attained considerable attention in recent years due to their great technological importance in fuel cell technology. Nanoengineering of the architectures of known materials and adopting composite approach can effectively enhance the active sites for electrode reactions. The use of nanotechnology will make SOFCs environment friendly and sustainable through green manufacturing processes of nanotechnology. Overviews of the contributions of nanotechnology and power electronics technologies to SOFCs, the transition of SOFCs from macro- to nanotechnology, the significance of nanomaterials in SOFCs, dynamic modeling, the function of optimization techniques, and the requirement for power electronics converters in SOFCs are all provided in this piece of work. The applications of SOFCs in different sectors, prominent institutes/labs and companies involved in SOFCs’ research, future challenges, and perspectives are also highlighted.
Keywords: Power Electronics; hydrogen energy; future perspectives; power electronics technology; SOFC modeling; nanotechnology; fuel cells; fi=Sähkötekniikka|en=Electrical Engineering|